Case report: Steroid-responsive acute chorea as first presentation of the coexistence of Moyamoya and Graves' disease - Wang, Wei-Sheng; Wu, Shey-Lin; Chan, Wei-Chieh; Chen, Yen-Chung (Frontiers in Neurology, 2023)
Background Chorea is a movement disorder characterized by abrupt, rapid, and uncontrollable, random movements from one part of the body to another with motor impersistence. Sporadic chorea is rarely caused by either thyrotoxicosis or Moyamoya disease (MMD). Methods and results In this case report, we describe a female patient with chorea with the rare coexistence of Graves' disease and Moyamoya disease. Tc-99m ethyl cysteinate dimer (ECD) brain perfusion single-photon emission computed tomography (SPECT) showed mild to moderate hypoperfusion in bilateral frontal and left temporal regions. After administering dexamethasone 20 mg for 5 days, her choreic movement symptoms recovered rapidly. Conclusion Although uncommon, thyrotoxicosis and Moyamoya disease can co-occur, especially in Asian female adults. Excessive thyroid hormones contribute to the dysregulation of neurotransmitters in basal ganglia-thalamocortical circuits. Moyamoya disease is responsible for ischemic changes affecting the excitatory–inhibitory circuits between the basal ganglia and the neocortex. Under a state of coexistence, thyrotoxicosis exaggerates cerebral metabolism, aggravating the impaired cerebral perfusion induced by Moyamoya disease. Moreover, inflammatory reactions caused by thyroid autoantibodies may also promote the progression of Moyamoya disease. In our experience, treatment with steroids may not only synergize the anti-thyroid effect but may also be a way to modulate the neurotransmitters within the basal ganglia or restore cerebral perfusion. We suggest that evaluation of the thyroid function status in Moyamoya disease is essential.